2017
DOI: 10.1038/s41598-017-09823-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Centella asiatica (L.) Urb. on cognitive function and mood related outcomes: A Systematic Review and Meta-analysis

Abstract: Centella asiatica (L.) Urb. has been used as an herbal brain tonic for mental disorders and enhancing memory, but no review of the overall evidence of C. asiatica and cognitive function has been conducted. This study aims to determine the effects of C. asiatica on cognitive function and its related properties. The current systematic review includes five randomized controlled trials (RCTs) conducted to determine the effect of C. asiatica alone and six RCTs conducted to determine the effect of C. asiatica-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 44 publications
2
73
0
1
Order By: Relevance
“…These findings are also been supported by a previous study in which a significant improvement was reported in the executive functioning and working memory of 20 healthy Malaysian participants after 3 weeks of being supplemented with the Superulam capsules (a combination of ulam or traditional Asian vegetables extracts) . Another systematic review on the common ulam, Centella asiatica , was also reported in Thailand, where the herb was not only discovered for improving working memory and alertness, but also in relieving anger as well …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings are also been supported by a previous study in which a significant improvement was reported in the executive functioning and working memory of 20 healthy Malaysian participants after 3 weeks of being supplemented with the Superulam capsules (a combination of ulam or traditional Asian vegetables extracts) . Another systematic review on the common ulam, Centella asiatica , was also reported in Thailand, where the herb was not only discovered for improving working memory and alertness, but also in relieving anger as well …”
Section: Discussionsupporting
confidence: 78%
“…25 Another systematic review on the common ulam, Centella asiatica, was also reported in Thailand, where the herb was not only discovered for improving working memory and alertness, but also in relieving anger as well. 10 The high level of antioxidants and polyphenols in ulam 26 was also found to be a major contributor to the cognitive pathway, where the latter is known for attenuating apoptosis, removing reactive oxygen species, preventing oxidative stress that causes cognitive decline, 8 as well as initiating the activation of sirtuins in the regulation of the human body cells that alleviates the occurrence of neurodegenerative illnesses. 27 Also, the flavonoid from the plants would scavenge for free radicals and decrease the neuron apoptosis that impedes neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing memory retention [34] and promoting longevity, this neurodegenerative adaptogen also helps in preventing cognitive impairments and alleviating oxidative stress associated with AD due to its antioxidant properties [35]. It is an alternative for acetylcholinesterase inhibitors, which generally comprise the first-line of treatment for AD and can also help in lowering the phospholipase A 2 activity [36]. A natural process that plays a role in causing neurodegeneration, i.e., mitochondrial dysfunction, can be altered by the antioxidant activity of this herb [37].…”
Section: Centella Asiatica (Mandukaparni)mentioning
confidence: 99%
“…However, most of the studies reported that pegaga capsule supplementation could improve working memory, alertness and relieve anger. This result was obtained from a systemic review article which reviewed 11 articles related to relationship between pegaga consumption, particularly capsule supplementation with cognitive function and mood (Puttarak et al 2017). Pegaga had been consumed to control anxiety as it helps in relaxation and mental calmness by inhibiting phospholipase substrate 2 activities in rat's cerebellum (Wijeweera et al 2006).…”
Section: Role Of Polyphenols In Improving Cognitive Declinementioning
confidence: 99%